Notational analysis in top level table tennis: A case study - Malagoli Lanzoni, I.; Di Michele, R. (Proceedings Book of The 15th ITTF Sports Science Congress Düsseldorf, 27th - 28th May 2017, 2017)
Notational analysis is a key tool to assess top-level Table Tennis players during competition and training. This study aimed to analyse a selection of technical/tactical indicators during top-level Table Tennis matches. Eight matches of a top-level Table Tennis player (TTP), played against eight different opponents (OPP) in 2013-2014 international tournaments were randomly selected. A complete set of performance indicators were collected by video analysis: shots, footwork, impact position of the ball on the table and rally outcome. The shot most used by TTP was topspin (26.4%), followed by service (21.9%), push (19.0%), block (15.0%), top c. top (11%), flick (6.0%) and others (2.0%). When considering forehand (-F) and backhand (-B) shots, TTP preferred to play topspin-F (20.0%), push-F (15.0%), block-B (14.2%), topspin-B (13.5%), and top c. top-F (12.3%). OPP showed similar shot distributions.The distribution of footwork for TTP was: one step (37.0 %), chassè (21.0%), no step (18.0%), crossover (11.2%) and pivot (11.2%), while for OPP the distribution was: one step (37.0%), no step (24.0%), chassè (18.0%), crossover (10.0%) and pivot (6.5%). Concerning the area, TTP received serves mostly in area 3 (54%), 2 (25.0%), and 5 (5.0%), while he served mostly in area 2 (42%), 3 (30.0%), and 5 (17.0%). Finally, winning shots for TTP were topspin-F (39.0%), topspin-B (19.0%), while TTP errors were top spin-F (19.0%), block-B (19.0%), top c. top-F (18.0%). In conclusion, these findings show how a thorough analytical approach based on notational analysis may be effective for performance assessment of top-level professional players.